SAR studies of 9-norbornylpurines as Coxsackievirus B3 inhibitors - Sála, Michal; De Palma, Armando M; Hřebabecký, Hubert; Dejmek, Milan; Dračínský, Martin; Leyssen, Pieter; Neyts, Johan; Mertlíková-Kaiserová, Helena; Nencka, Radim (Bioorganic & medicinal chemistry letters, 2011)
Coxsackievirus and related enteroviruses are important human pathogens that cause various diseases with clinical manifestations ranging from trivial flu-like syndromes to dangerous or even fatal diseases such as myocarditis, meningitis and encephalitis. Here, we report on our continuous SAR study focused on 9-(bicyclo[2.2.1]hept-2-yl)-9H-purines as anti-enteroviral inhibitors. The purine moiety was modified at positions 2, 6 and 8. Several analogues inhibited Coxsackievirus B3 as well as other enteroviruses at low-micromolar concentrations. The 6-chloropurine derivative was confirmed as the most active compound in this series.
Keywords: Vero buňky; Cercopithecus aethiops; Animals; Antiviral Agents; Vero Cells; Structure-Activity Relationship; puriny; antivirové látky; vztahy mezi strukturou a aktivitou; Chlorocebus aethiops; Enterovirus; Purines; zvířata